1975
DOI: 10.1111/j.1471-4159.1975.tb03655.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylases of Myelin Basic Protein and Histone in Rat Brain

Abstract: —The two enzymes methylating myelin basic protein and histone were purified 170‐ and 250‐fold respectively from the cell sap fraction of rat brain. These enzymes methylated only arginine residues of the two proteins. The enzyme activities were present in all organs tested. Testis has the highest, brain a moderate and liver the lowest activity. Most of the activities were present in the cell sap fraction in brain, liver and testis. Methylation of myelin basic protein and histone was examined in both the cell sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The histone IIAS methylase exhibits a fall in activity during the first 4 weeks after birth. This postnatal fall in activity agrees well with that reported for the cytoplasmic histone (arginine) methylase in rat brain (Miyake, 1975). The twofold increase in MBP methylase over the same period is J .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The histone IIAS methylase exhibits a fall in activity during the first 4 weeks after birth. This postnatal fall in activity agrees well with that reported for the cytoplasmic histone (arginine) methylase in rat brain (Miyake, 1975). The twofold increase in MBP methylase over the same period is J .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a protein (arginine) methyltransferase has been purified from calf brain; it methylates both myelin basic protein and histone, type IIAS [prepared from calf thymus by extraction in 1 M NaCI, precipitation in HzO, acid extraction and reprecipitation with ethanol], with a relative efficacy of 1 to 3 (Lee et al, 1977). However, it has been suggested that myelin basic protein and histone, type IIAS are each methylated by a different specific protein (arginine) methylase (Miyake and Kakimoto, 1973;Miyake, 1975). Attempts to demonstrate an increase in myelin basic protein methyltransferase with the period of active myelination in the brain have produced conflicting reports (Paik and Kim, 1973;Jones and Carnegie, 1974;Miyake, 1975).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, Miyake (1975) and Crang and Jacobson (1982), employing developing rat brain and mouse spinal cord. respectively, demonstrated a parallel increase of MBP-PM1 during active myelination, whereas histone-PM1 activity decreased during this period.…”
Section: Protein Methylase I Actioity During Brain Developmentmentioning
confidence: 99%
“…Miyake (1975) has further characterized two methylases from brain. Although there are two possible dimethylarginine isomers, Na,N ·a~ dimethylarginine (unsymmetrical dimethylarginine) or NG,NG-dimethylarginine (symmetrical dimethylarginine), it is likely that only the unsymmetrical isomer is present in the myelin basic protein (Baldwin and Carnegie, 1971b).…”
mentioning
confidence: 99%